European water recreation values - A systematic review and meta-analysis of travel cost studies published between 2000–2021 - Artell, Janne; Juutinen, Artti; Kostensalo, Joel; Lankia, Tuija; Pouta, Eija; Ahtiainen, Heini; Tolvanen, Anne (Elsevier, 2025)
European surface waters provide a wide variety of opportunities for outdoor recreation. Also, the economic value of the waters has been extensively studied over the last few decades. We conducted a systematic literature review and meta-analysis of the European water recreation that examined the travel cost valuation studies published between 2000 and 2021. Following the well-established PRISMA guidelines, we found 40 separate studies with a total of 85 consumer surplus estimates based on data from over 113,000 persons. The data were analysed using 1) a multilevel random-effects model for estimating the average consumer surplus of a trip and 2) a meta-regression model with publication year, region, GDP per capita, multi-day trips and the type of recreation were included as covariates. The potential presence of publication bias was tested using Eggert's test. Studies on multiday trips and a variety of water recreation activities were observed to provide larger value estimates than studies focusing on specific single-day activities. In-water activities, such as boating, were more highly valued than activities in the vicinity of water, such as recreational activities on a beach. The average consumer surplus (CS) per trip was €158 (95 % C.I. [€107, €232]) in year 2019 PPP-corrected EU-27-country euros. No statistically significant differences in consumer surplus were found across regions. The average CS was also not found to have changed over the study period adjusted for inflation.
Keywords: water-based recreation; consumer surplus; meta-analysis; Europe; travel cost method